Cidadania docente universitária: sua relação com o desempenho dos estudantes - Arménio Rego (Universidade do Minho, 2000)
The study aims at showing how citizenship behaviors of university teachers (CBUT) explain students´ academic performance. 249 students reported four CBUT dimensions (participatory behavior, practical orientation, conscientiousness and courtesy) of a teacher of their choice. Two months later, they sent to the researcher the mark obtained in the discipline taught by the choosen teacher. The findings show that only courtesy explains students academic performance. This evidence contrasts with previous research in wich independent and dependent variables were collected simultaneously.